2013
DOI: 10.1016/j.ahj.2012.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Marijuana use and long-term mortality among survivors of acute myocardial infarction

Abstract: Background Smoking marijuana has been reported to increase risk of myocardial infarction (MI) immediately after use, but less is known about the long-term impact of marijuana use among patients with established coronary disease. Methods The Determinants of MI Onset Study (MIOS) is a multicenter inception cohort study of MI patients enrolled in 1989–1996 and followed for mortality using the National Death Index. In an initial analysis of 1935 MI survivors followed for a median of 3.8 years, we found an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 28 publications
2
53
0
4
Order By: Relevance
“…Nonetheless, there is a possible increased risk of mortality for patients who have already had a past myocardial infarction compared with marijuana smokers that did not 87. Some early studies concluded that marijuana users do not have a significantly increased risk of stroke and heart failure later showed that those risks were significant upon longer follow up with multivariable analysis showing greater relative risk of myocardial infarction the younger group 3, 88. The CARDIA cohort study which spanned 25 years showed no association of marijuana use with CVD or atherosclerosis risk 5, 6.…”
Section: Exogenous Cannabinoids and Cvd: Paradoxes And Therapeutic Pomentioning
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, there is a possible increased risk of mortality for patients who have already had a past myocardial infarction compared with marijuana smokers that did not 87. Some early studies concluded that marijuana users do not have a significantly increased risk of stroke and heart failure later showed that those risks were significant upon longer follow up with multivariable analysis showing greater relative risk of myocardial infarction the younger group 3, 88. The CARDIA cohort study which spanned 25 years showed no association of marijuana use with CVD or atherosclerosis risk 5, 6.…”
Section: Exogenous Cannabinoids and Cvd: Paradoxes And Therapeutic Pomentioning
confidence: 99%
“…The CARDIA cohort study which spanned 25 years showed no association of marijuana use with CVD or atherosclerosis risk 5, 6. Furthermore, many studies have been inconclusive and suggest that further research on a larger scale with repeated measures are needed 3, 4, 7. Despite the possible CVD risks associated with marijuana use, there is rational potential for modulation of the ECS using exogenous cannabinoids derived from plants or synthetic sources, as single drugs or complex mixtures, for treatment of disease in the CVD space.…”
Section: Exogenous Cannabinoids and Cvd: Paradoxes And Therapeutic Pomentioning
confidence: 99%
See 1 more Smart Citation
“…En nuestro país se estiman prevalencias de 7,1% y 0,9% para el consumo de cannabis y cocaína respectivamente entre los 12 y los 25 años 2 , desconociéndose la prevalencia de consumo de estas sustancias en la población general. El consumo agudo o crónico de ambas DI ha sido descrito como factor de riesgo de infarto agudo del miocardio (IAM), miocardiopatías y arritmias cardiacas, describiéndose diversos mecanismos fisiopatológicos involucrados en la injuria miocárdica por drogas [3][4][5][6] . Las recomendaciones del manejo del IAM en estos pacientes se basan fundamentalmente en opiniones de expertos 5 , siendo escasas las experiencias sobre el manejo de esta subpoblación y su evolución posterior.…”
unclassified
“…
, rAmÓn corbAlán 3,6 . GruPo de estudio multicéntrico del infArto (Gemi) Characteristics, management, and outcomes of illicit drug consumers with acute myocardial infarction (86.3% and 42.5% respectively, p < 0.01).
…”
mentioning
confidence: 99%